2020
DOI: 10.5114/wo.2020.99025
|View full text |Cite
|
Sign up to set email alerts
|

Adenoid cystic carcinoma of the breast – an uncommon malignancy with unpredictable clinical behaviour. A case series of three patients

Abstract: Adenoid cystic carcinoma (AdCC) is a common tumour of the minor salivary gland, rarely seen in other anatomical locations. In particular, AdCC of the breast accounts for < 0.1% of patients diagnosed with breast cancer. Here we report our institutional experience with three cases of breast AdCC diagnosed between 2009 and 2017. Mean age of women included in the report was 53 (range from 41 to 62). One case was of no special subtype, two were solid variants and one presented with a component of invasive ductal ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The mainstay of treatment of ACCB has not yet been established due to its rare incidence and indolent behavior, which can be confirmed in the literature, as there are mainly case reports, [7][8][9][10][11] or small series. 2,3,12,13 Regarding histological classification, several scores can be applied. Ro et al suggested a division into 3 prognostic groups, according to architectural and cytological features, namely the proportion of solid and cystic components: grade 1 if there is a predominance of glands and cystic components and absence of solid ones; grade 2 when there are less than 30% of solid components; and grade 3 if there are more than 30% of solid components.…”
Section: Introductionmentioning
confidence: 99%
“…The mainstay of treatment of ACCB has not yet been established due to its rare incidence and indolent behavior, which can be confirmed in the literature, as there are mainly case reports, [7][8][9][10][11] or small series. 2,3,12,13 Regarding histological classification, several scores can be applied. Ro et al suggested a division into 3 prognostic groups, according to architectural and cytological features, namely the proportion of solid and cystic components: grade 1 if there is a predominance of glands and cystic components and absence of solid ones; grade 2 when there are less than 30% of solid components; and grade 3 if there are more than 30% of solid components.…”
Section: Introductionmentioning
confidence: 99%